PENGARUH MODEL LOK-R BERBANTUAN QUESTION BOX TERHADAP BERPIKIR KRITIS DAN SELF-AWARENESS SISWA SMP - Rositi Yola Julianti; Sri Anggoro, Bambang; Dinda Pratiwi, Dona (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effect of the LOK-R instructional model—which consists of Literacy, Orientation, Collaboration, and Reflection—combined with the Question Box media on students’ mathematical critical thinking skills and self-awareness. The research employed a quasi-experimental design using a posttest-only control group approach. The participants were three eighth-grade classes: the first experimental group was taught using the LOK-R model with the Question Box media, the second group received instruction with the LOK-R model only, and the control group was taught using Direct Instruction. Data were collected using essay tests to assess critical thinking and Likert-scale questionnaires to measure self-awareness. A MANOVA analysis yielded a Wilks’ Lambda value of 0.254 with a significance level of 0.000, indicating a statistically significant multivariate effect of the instructional model. The highest mean critical thinking score was observed in the first experimental group (76.13; SD = 4.864), followed by the second experimental group (67.47), and the control group (58.58). These findings demonstrate that integrating the LOK-R model with the Question Box media is more effective in enhancing both critical thinking and self-awareness among students.